Structural and dielectric properties of Ba0.5Sr0.5(SnxTi1-x)O-3 ceramics obtained by the soft chemical method - Souza, I. A.; Cavalcante, L. S.; Sczancoski, J. C.; Moura, F. [UNESP]; Paiva-Santos, C. O. [UNESP]; Varela, José Arana [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2009)
Ba0.5Sr0.5(SnxTi1-x)O-3 ceramics with different compositions (x = 0, 0.05, 0.10 and 0.20) were synthesized by the soft chemical method. X-ray diffraction patterns and Rietveld refinements revealed that these ceramics crystallize in a cubic structure. Secondary phases (BaSnO3) were verified in Ba0.5Sr0.5(SnxTi1-x)O-3 ceramics with Sn content x >= 0.10. Raman spectra indicated a reduction in the Raman-active modes with the increase of Sn content in the lattice. Dilatometric measurements were used to analyze the sintering temperature behavior of these materials. Dielectric properties were investigated as a function of applied frequency. The increase in the remanent polarization was attributed to the imprint phenomenon due to the formation of oxygen vacancies. The domain pinning and the formation of BaSnO3 phase favored the increase in the coercive fields. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Dielectric; X-ray diffraction